Clinical caritas process applied to paraplegic client with pressure ulcers - Medeiros, Fabíola de Araújo Leite; França, Inacia Sátiro Xavier de; Sousa, Francisco Stélio de; Baptista, Rosilene Santos (Rev Rene, 2012)
Pressure ulcers are necrotic lesions, common in the skin and subcutaneous tissue overlying bony prominences. We aimed to apply caritas processes to paraplegic client with pressure ulcers, analyzing the potential of this process to achieve an ethical, moral and human care. This is a case study that used as instruments for data collection an interview, evaluation form and application of a nursing care process. Data were categorized according to the ten elements of clinical caritas. After 40 days of care, the client was discharged, with reduction of infection risk and general condition improvement. The study evidenced that a humanistic and phenomenological approach helps with the nursing process and contributes to the interpersonal relationship between caregiver and client.